The orchestrated feature of Cornus kousa fruit and gut microbiota against obesity via integrated pharmacology - Ki‐Kwang Oh; Sang‐Jun Yoon; Sang Youn Lee; Satya Priya Sharma; Sung‐Min Won; Jin‐Ju Jeong; Dong Joon Kim; Ki‐Tae Suk (Food Frontiers)
Abstract Cornus kousa fruit (CKF) has been utilized as anti‐obesity supplementation in East Asia, including Korea, and gut microbiota (GM) might have synergistic effects on obesity (OB) via its interplay. We aimed to decode molecule(s), mechanism(s), and target(s) on interplay between CKF and GM via network pharmacology analysis. The final targets were analyzed by protein–protein interaction (PPI) networks and a bubble plot. The GM interacted with significant targets identified by the gutMGene database. The relationships among CKF or GM, signaling pathways, targets, and molecules (CGSTM) were plotted by R package. Finally, molecular docking assay and density functional theory (DFT) were performed to validate its affinity. The final targets (22) were selected on OB‐responded targets, indicating that interleukin‐6 (IL6) was the most crucial protein‐coding target on PPI networks. A bubble plot and CGSTM networks suggested that the advanced glycation end‐receptor for advanced glycation end products signaling pathway in diabetic complications is inhibited by CKF and peroxisome proliferator–activated receptor (PPAR) signaling pathway is activated by GM. As the most stable conformers, IL6‐equol complex was attributed to GM, and PPAR alpha‐linoleic acid, PPAR delta‐stearic acid, and fatty acid–binding protein 4‐dimethyl 2,3‐bis(1,3‐dimethylindol‐2‐yl) fumarate complex were attributed to CKF. Noticeably, stearic acid was removed by DFT analysis; all other three molecules were proposed as good electron donators with the higher electronegativity compared with a standard drug (Orlistat). This study shows that integrated pharmacological analysis can enable to decode the unknown relationships between CKF and GM. Overall, this study reveals that the combination of CKF and favorable GM might exert dual therapeutic effects on OB.